Longitudinal predictors of domestic violence perpetration and victimization: A systematic review. (September 2015) - Costa, Beth M.; Kaestle, Christine E.; Walker, Arlene; Curtis, Ashlee; Day, Andrew; Toumbourou, John W.; Miller, Peter
Abstract: Domestic violence (DV) is a serious and complex social issue which is associated with significant costs to both those individuals who are directly affected and the wider community. Preventative approaches with vulnerable population groups represent an important component of any integrated response to DV and should be informed by an understanding of those factors that influence violence developmentally. This paper reports the findings of a systematic review of longitudinal studies that have prospectively investigated childhood and/or adolescent predictors of DV perpetration and/or victimization among adult men and women in intimate relationships. We identified 25 original studies that met the inclusion criteria, all of which investigated predictors of domestic physical abuse. Few studies prospectively examined psychological, sexual and verbal abuse. Child and adolescent abuse, family of origin risks, child and adolescent behavioral problems, adolescent peer risks, and sociodemographic risks were all identified as significant predictors of DV perpetration and victimization. It is concluded that early childhood and adolescent factors are consistent predictors in the development of DV perpetration and victimization and that prevention and early intervention approaches targeting these factors are likely to prove the most effective. Highlights: We review prospective longitudinal studies of child and adolescent predictors of DV. We identify five common predictors of DV perpetration and victimization for men and women. Most consistent predictors of DV are child abuse and family of origin risks. Additional predictors are child/adolescent behavior problems and sociodemographic risk. Policy, intervention and research need to adopt a whole of life approach to addressing DV.